PENDIDIKAN DALAM PEMIKIRAN AL-GHAZALI - Muhammad Edi Kurnanto (The Pontianak State Institute of Islamic Studies, 2011)
This article describes Al-Ghazali’s thoughts on education regarding the concept of mankind. His preferred form of education was in line with his concept of mankind. Education, in Al-Ghazali’s opinion, can be viewed from the individual, societal, and psychological sides. From the individual side, education is seen as developing divine characters in humans in line with their promise to Allah and their guidance to science and revelation. Humans long for submission to Allah, and their main struggle in life is to develop divine characters in themselves according to their capacity.